Large compositional differences in the gases released from the Kizildag ophiolitic body (Turkey): Evidences of prevailingly abiogenic origin. (January 2018) - D'Alessandro, Walter; Yüce, Galip; Italiano, Francesco; Bellomo, Sergio; Gülbay, Ahmet H.; Yasin, Didem U.; Gagliano, Antonina Lisa
Abstract: We investigated the geochemical features of the gases released from the Kizildag ophiolitic complex (Hatay, Turkey). Twenty-three samples both dissolved in hyperalkaline waters and free gases (bubbling gases and dry seeps) were collected. Samples were analysed for their chemical (He, H2, O2, N2, CH4 and CO2 ) and isotopic (He, δ 13 C-CH4, δ 2 H-CH4, δ 2 H-H2 ) composition including the content and C-isotopic composition of C2 to C5 alkanes in free gases. Analytical results evidence H2 production through low-temperature (<80 °C) serpentinization processes and subsequent abiogenic CH4 production through Fischer-Tropsch-type reactions. In some sample small additions of methane either of microbial or of thermogenic origin can be hypothesized. At one of the sites (Kisecik) a clear fractionation pattern due to microbial methane oxidation leading to strongly enriched isotopic values (δ 13 C +15‰ and δ 2 H −68‰) and depletion in methane concentrations has been evidenced. At the dry gas seep of Kurtbagi methane flux measurements have been made and a preliminary output estimation of about 1000 kg per year has been obtained. Highlights: Gases collected from dry seepages and bubbling or dissolved in springs of the ophiolitic body of Kizildag (Turkey). Large compositional variation (H2 - CH4 or N2 -dominated) Hydrogen derives from low temperature serpentinization processes Methane mainly derives from abiotic processes Large isotopic fractionation of methane at one site due to biological oxidation